2020
DOI: 10.1093/gji/ggaa519
|View full text |Cite
|
Sign up to set email alerts
|

Empirical formula for the quality factors of crack resonances and its application to the estimation of source properties of long-period seismic events at active volcanoes

Abstract: Summary Long-period (LP) seismic events at active volcanoes are thought to be generated by oscillations of fluid-filled resonators. The resonator geometry and fluid properties of LP sources have been estimated by comparing observed frequencies and quality factors (Q) with those calculated by numerical simulations with a crack model. A method to estimate all the parameters of crack geometry and fluid properties using an analytical formula for crack resonance frequencies has recently been proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…A similar model has been proposed at Galeras volcano, with LP events suggested to represent the propagation and increase in volume of a vertical crack injected by a gas-ash mixture (Taguchi et al, 2018). Both the crack volume and mass fraction of gas within the crack were inferred to have decreased as ash was deposited and welded before the next LP event (Taguchi et al, 2021). We propose that the Húsafell tuffisite represents the fossil record of exactly this type of LP seismic swarm.…”
Section: Tuffisites As a Seismic Sourcesupporting
confidence: 64%
See 1 more Smart Citation
“…A similar model has been proposed at Galeras volcano, with LP events suggested to represent the propagation and increase in volume of a vertical crack injected by a gas-ash mixture (Taguchi et al, 2018). Both the crack volume and mass fraction of gas within the crack were inferred to have decreased as ash was deposited and welded before the next LP event (Taguchi et al, 2021). We propose that the Húsafell tuffisite represents the fossil record of exactly this type of LP seismic swarm.…”
Section: Tuffisites As a Seismic Sourcesupporting
confidence: 64%
“…To produce long-lasting oscillations with Q significantly greater than 100, there needs to be a large density difference between the fluid and the surrounding rock (Chouet, 1996). Computed synthetic waveforms for fluid-filled cracks indicate that very high Q-values (e.g., Q = 400 at Tungurahua Volcano, Molina et al, 2004) are best explained if the fluid is a dusty or misty gas with low sound speed (Kumagai and Chouet, 2000;Taguchi et al, 2021). In this volcanic scenario, the dust is inferred to be fine-grained particles of volcanic ash.…”
Section: Tuffisites As a Seismic Sourcementioning
confidence: 99%
“…However, it is possible that the first two spectral peaks in the seismic data do not correspond to the fundamental mode and first higher mode if any of them are not properly excited. For instance, previous studies of VLP and LP events (Kumagai, 2006;Taguchi et al, 2018Taguchi et al, , 2021 indicated that the observed lowest frequencies were not the fundamental mode. To examine this hypothesis, we compute the frequency ratios between the first 5 resonant modes and the ratios between the first 4 longitudinal modes of a rectangular crack with varying C L and aspect ratios α (see Tables S7-S10 in the Supporting Information S1).…”
Section: Application To Vlp Seismic Signals During the Mayotte Volcan...mentioning
confidence: 94%
“…While brittle failure earthquakes occur in these areas, pressure changes in fluid‐filled cavities can produce other types of signals. At volcanoes, LP events, as a low‐frequency signal with the resonant property, have been interpreted to be the far‐field seismic response of oscillations of fluid‐filled cavities during fluid transport, and therefore, it serves as an important eruption precursor (Chouet, 1986; Chouet & Matoza, 2013; Liang et al., 2020; Taguchi et al., 2021; Waite et al., 2013). Due to this low resonant frequency, researchers relate LP events to a slow wave trapped in fluid‐filled fractures called the Krauklis wave that contains the same resonance information about the fracture and fluid properties (Gräff et al., 2019; Lipovsky & Dunham, 2015; Tary et al., 2014).…”
Section: Introductionmentioning
confidence: 99%